Novel developments in uncertainty representation and processing : advances in intuitionistic fuzzy sets and generalized nets : proceedings of 14th International Conference on Intuitionistic Fuzzy Sets and Generalized Nets /: advances in intuitionistic fuzzy sets and generalized nets : proceedings of 14th International Conference on Intuitionistic Fuzzy Sets and Generalized Nets. ([2016]) - Unknown
No abstract available